The accuracy of warfarin dosage based on VKORC1 and CYP2C9 phenotypes in a Chinese population (Faculty of Medicine Universitas Indonesia, 2012)
Background: The aim of this study is to assess the accuracy of warfarin dosage based on VKORC1 and CYP2C9 genotype in Chinese population. Methods: Blood samples were taken from 37 patients. We compared the warfarin dosage obtained from genotype (according to www.warfarindosing.org) and treatment dosage with international normalized ratio (INR) value within 2.0-3.0. Results: The majority of Chinese people in our study are VKORC1 homozygous AA (89.2%), rarely VKORC1 heterozygous AG and we cannot find a patient with homozygous GG. For CYP2C9 genotype, most patients have the wildtype variants (CYP2C9*2 CC and CYP2C9*3 AA). The warfarin dosage for patients with VKORC1 AA and CYP2C9*3 AC is lower than for patients with other genotype variants. Conclusion: There is no significant difference between pharmacogenetic algorithm (www.warfarindosing.org) and our treatment dosage. Our conclusion is that the pharmacogenetic algorithm is accurate to predict the warfarin dose. (Med J Indones. 2012;21:108-12)